Pompeian Artifacts and Jesus-Devotion: The Contours of the Issue in the Early Twenty-First Century - Longenecker, Bruce W. (Vigiliae Christianae, 2019)
Certain Pompeian artifacts have drawn debate as to whether they might be the product of Jesus-devotion within the walls of that small town. This article overviews the context for considering that issue in accordance with the best forms of current historiographical analysis and in light of the full spread of the evidence. To do otherwise is to mire the debate in a problematic web of outdated assumptions. When those assumptions are purged from the interpretive process and the full spread of evidence is taken into account, new interpretive possibilities open up, with important historical implications for our understanding of early forms of Jesus-devotion.